Dupilumab for the treatment of prurigo nodularis: A systematic review - Cao, Peng; Xu, Wenjing; Jiang, Shuyi; Zhang, Litao (Frontiers in Immunology, 2023)
Background: Conventional treatment techniques have limited efficacy and more side effects in the treatment of prurigo nodularis. The better alternative treatment option for better outcomes of the disease is dupilumab. Objective: The objective of this study was to systematically review dupilumab-related treatment outcomes in prurigo nodularis. Methods: Several databases like Embase, PubMed, Web of Science, and Cochrane library were searched for data acquisition on October 8, 2022. Based on Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines, 24 publications were included in this study. Results: After 4,12,16 and more than 16 weeks of dupilumab treatment, 8.3% (n=5/60), 34.4% (n=11/32), 3.6% (n=2/56), and 45.3% (n=29/64) of patients had complete remission, respectively. In addition, 85.0% (n=51/60), 59.4% (n=19/32), 83.9% (n=47/56), and 43.8% (n=28/64) had partial remission, respectively. Moreover, 6.7% (n=4/60), 6.3% (n=2/32), 12.5% (n=7/56), and 10.9% (n=7/64) showed no remission, respectively, and significant reduction of numeric rating scale itch intensity (from 9.0 to 4.9, 2.1, 2.8, 0.9) was attained. There were no serious adverse events observed during treatment, but the most common event observed was conjunctivitis (12.6%, n=15/119). Conclusions: Dupilumab has definite effectiveness and safety in prurigo nodularis treatment.